An assessment of cycling and bicycle lanes along Marcos Highway - Acma, Karen Ann L.; Regidor, Jose Regin F. (Quezon City College of Engineering, University of the Philippines Diliman, 2016)
As part of the promotion of environmentally sustainable transport (EST), the use of non-motorized transport (NMT) was endorsed by the government. As a result, bicycle lanes along different parts of Metro Manila were constructed to encourage one of the most familiar forms of NMT, cycling. One of these lanes was placed along Marcos Highway to provide a safe place for cyclists to travel through the busy and high-speed highway. The main objective of this study is to determine if this existing bicycle lane is usable and if its efficiency is satisfactory. This was decided by collecting two different sets of data, static which was taken from the infrastructure itself and dynamic which came from the users. Data from the infrastructure was an inventory of the lane design requirements and the list of barriers present on the bicycle lanes. Data from the users was bicycle count of cyclists going through the highway. These count was characterized based on the cyclists preference and the type of cyclist, whether commuter or recreational. The infrastructure data was analyzed and compared to standards to determine its efficiency and usability while data from the users were graphed to determine trends. Both data were then correlated with each other to determine their relationship. Results showed that most stations in the lane comply with AASHTO and NACTO design guidelines but most stations had obstructions present along the lane which made it a lower choice for the users. It was recommended that a stricter implementation of existing laws be done especially for the no parking on bicycle lanes and the proper PUY stops. The lane signs must also be improved and properly maintained for better information for the cyclists. Stations should also be made to comply the guidelines for the better use of the cyclists. Further study might also consider the relocation of the lane to the outermost lane of the carriageway for an easier access of the lane.
Thesis (B.S. Civil Engineering)--University of the Philippines Diliman
Keywords: Bicycle lanes -- Philippines